PENGENDALI LAMPU KANTOR MENGGUNAKAN GOOGLE ASSISTANT DAN ADAFRUIT. IO BERBASIS NODEMCU ESP8266 - Dwiyatno, Saleh; Iskandar, Riki; Nuryani, Ely (Jurnal Ilmiah Sains dan Teknologi, 2021)
This study discusses the implementation of office light control automation implementedin the PT. TELECOMMUNICATION MENES BANTEN Banten Province, using googleassistant and adafruit.io based on nodemcu esp8266. In this era of developingtechnology, controlling automation is very much needed, because it can control andcontrol electronic devices easily and more efficiently. The problems faced by the PT.Telkom Menes Banten, namely still using the manual system on the push button switch on/ off to operate the lights and the lack of utilization of technological devices such as relays,nodemcu esp8266 and internet service providers. In this regard, the author tries to takeadvantage of technological devices and implement a tool, namely the automation of officelight controllers in the PT. Telkom Menes Banten. This research will explain about theimplementation carried out until the final result of the automation of office lightcontrollers in the PT. Telkom Menes Banten, so that it can be applied and used as areference for the future.